Design and Implementation of a Medical TeleMonitoring System based on IoT - Hamdani, M.; Youcefi, M.; Rabehi, A.; Nail, B.; Douara, A. (Engineering, Technology & Applied Science Research, 2022)
With the advancement of technology, healthcare and monitoring systems face significant issues. Internet of Things (IoT) in healthcare enables real-time health monitoring at a low cost. This paper aims to provide a medical telemonitoring system based on IoT for healthcare applications for doctors and paramedical staff. The system is made up of many sensors that can capture electrocardiograms (ECGs) in real-time and measure the temperature of the human body. The designed circuit is implemented and the obtained results are analyzed and discussed.